The Use Of Remote Sensing For Mangrove Ecosystem.Monitoring In Segara Anakan Central Ja Va - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The paper deals with an actual condition of mangrove ecosystem in Segara Anakan Central Java by analysing them from remote sensing satellite image such as SPOT XS and Landsat 1M recorded in between 1981 and 2003. Digital and manual image analysis were applied Field checks were conducted in 199 3 and in 2005. The result show that three aspects of mangrove ecosystem can be studied from the remote sensing data, i.e. mangrove zonation, land cover changes and mangrove physical ecosystem changes. In mangrove zonation, it showed that three to four zones in mangrove forest zonation can be identified by satellite digital data analysis, especially in accretion areas. Mangrove of these areas actually suffers from human pressures, mainly for fishery and agriculture activities, and environmental changes. Lagoon morphometric decreased considerably and its influenced the existence of the mangroves. Mangrove extend in Segara Anakan, the mangrove forest covers 8600ha in 1987 and 7500ha in 1998, and in 2008 it decreased considerably. The lagoon of Segara Anakan undergoes to be disappeared by sedimentation processes from its hinterland In consequence mangrove ecosystem in the region is in dangerous condition Keywords: remote sensing, mangrove forest, ecosystem degradation